Neopestalotiopsis cavernicola sp. nov. from Gem Cave in Yunnan Province, China - Liu, Xiangfu; Tibpromma, Saowaluck; Zhang, Fan; Xu, Jianchu; Chethana, K.w.t.; Karunarathna, Samantha C.; Mortimer, Peter E. (Phytotaxa, 2021)
In this paper we describe a new species of cave fungus belonging to Sporocadaceae (Amphisphaeriales), collected from Gem Cave, Fumin County, Yunnan Province, China. Initial morphological observations confirmed that our fungal collection is a pestalotioid species. Phylogenetic analyses of combined internal transcribed spacer (ITS), β-tubulin (TUB) and translation elongation factor 1-alpha (TEF1α) gene sequence dataset confirmed that our fungus forms an independent branch within Neopestalotiopsis. Thus, we describe our fungus as a new species of Neopestalotiopsis based on both morphology and multigene phylogeny. This is the first-ever report of Neopestalotiopsis from a cave habitat. A full description, micrographs and a phylogenetic tree showing the placement of the new species are provided.